Strategic Planning Process and Organizational Structure: Impacts, Confluence and Similarities - Dyogo Felype Neis; Maurício Fernandes Pereira; Emerson Antonio Maccari (BBR: Brazilian Business Review)
This article aims to analyze the relationship between the strategic planning process and organizational structure in the reality of a complex organization: the Public Prosecutor’s Office of Santa Catarina (MPSC). The research is set by the single case study research strategy and data were collected through the following instruments: bibliographical research, documentary research, semi-structured interviews and systematic observation. The conclusion indicates that the phases of the strategic planning process influence and are influenced by the elements of the organizational structure and highlights the confluences, the impacts and similarities between the stages of formulation and implementation of the strategic process with the various constituent elements of the organizational structure.